2016
DOI: 10.21786/bbrc/9.3/14
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of job stress with self-ef cacy among nurses working in hospitals of Semnan University of Medical Sciences, Iran

Abstract: The individual's perception of stress is essential in its experience and on the other hand, the same stressful events create different effects in people, so the question is whether capable nurses have more or less stress? This study was conducted to determine the relationship between self-effi cacy and job stress among nurses. Participants in this study were nursing staffs of affi liated hospitals of Semnan University of Medical Sciences in Iran in 2015-2016. The results showed that 62.7% of the nursing staffs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 10 publications
1
11
1
Order By: Relevance
“…A high score reflects high job stress, and a low score reflects low stress. The reliability of the tool with Cronbach’s alpha coefficient was obtained 0.85, 0.87, 0.75, 0.63, 0.73, 0.92 in the mentioned dimensions, respectively, which confirmed Mehdizadeh et al’s research (2013) [14]. In the current study, the tool validity was confirmed using face and content validity and its reliability by using the test re-test method was confirmed by a score of 99%.…”
Section: Methodssupporting
confidence: 80%
“…A high score reflects high job stress, and a low score reflects low stress. The reliability of the tool with Cronbach’s alpha coefficient was obtained 0.85, 0.87, 0.75, 0.63, 0.73, 0.92 in the mentioned dimensions, respectively, which confirmed Mehdizadeh et al’s research (2013) [14]. In the current study, the tool validity was confirmed using face and content validity and its reliability by using the test re-test method was confirmed by a score of 99%.…”
Section: Methodssupporting
confidence: 80%
“…All the above could explain the higher GSES. It has also been identified in accumulative studies that higher GSES was negatively associated with depression and anxiety [ [43] , [44] , [45] ]. This might also explain the results in nurses of current study, which the self-efficacy was in the upper middle level and negatively correlated with anxiety and depression ( Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that the proportion of nurses with job stress ranged from 37.8–74.8% in different countries or regions and the degree of nurses’ job stress was always medium or above (Mahdizadeh, Daihimfar, & Kahouei, ; McTiernan & McDonald, ; Poursadeghiyan et al, ; Salilih & Abajobir, ; Xie et al, ). In the process from job stress to depression and anxiety, numerous factors including social support, self‐efficacy, coping strategies, job burnout, etc., have been explored (Karkar, Dammang, & Bouhaha, ; Khamisa et al, ; Lu et al, ; Mahdizadeh et al, ; Wu et al, ; Yu et al, ). These factors play an important role in the link between job stress and depression and anxiety and significantly affect health outcomes of nurses.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, self‐efficacy is a kind of personality factor in Bandura's social cognitive theory (Bandura, ), having an impact on the behaviour, effort, and time spent for dealing with environmental stress (Mahdizadeh et al, ; Olson & Hergenahahn, ). Significant negative relationships have been found between job stress and self‐efficacy (Mahdizadeh et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation